2020
DOI: 10.1002/poc.4068
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of trans‐2‐(azaarylsulfanyl)‐cyclohexanols as potential pH‐triggered conformational switches

Abstract: A series of trans‐2‐(azaarylsulfanyl)‐cyclohexanols, structurally similar to previously studied trans‐2‐aminocylohexanols, have been synthesized and explored as conformational pH triggers. 1H NMR spectroscopy was used to estimate the position of the chair‐chair conformational equilibrium and its acid‐induced shift towards the conformer with the azaarylsulfanyl and hydroxy groups in equatorial positions due to an intramolecular hydrogen bond and electrostatic interactions. Such acid‐induced transition may be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The recent study found that novel conformational switches, i.e., trans-2-(azaarylsulfanyl)cyclohexanols, can trigger the ring flip in a relatively low pH range (2.8 to 4.3). 45 Apart from changing the pH sensitivity, the higher polarity or larger size of the lipid head-group tends to decrease the size of the liposomes, while higher basicity of the head-group causes release of the liposomes to be triggered at higher pH values. 41 Moreover, longer lipid tails yield liposomes with higher encapsulation capacity, while shorter lipid tails lead to a faster leakage of the liposome in response to lowered pH.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…The recent study found that novel conformational switches, i.e., trans-2-(azaarylsulfanyl)cyclohexanols, can trigger the ring flip in a relatively low pH range (2.8 to 4.3). 45 Apart from changing the pH sensitivity, the higher polarity or larger size of the lipid head-group tends to decrease the size of the liposomes, while higher basicity of the head-group causes release of the liposomes to be triggered at higher pH values. 41 Moreover, longer lipid tails yield liposomes with higher encapsulation capacity, while shorter lipid tails lead to a faster leakage of the liposome in response to lowered pH.…”
Section: Short Review Synthesismentioning
confidence: 99%